Motivation for Digital Activism in the Save the KPK Movement in Indonesia - Rohid, Nibrosu; Sugihartati, Rahma; Suyanto, Bagong (Journal of Posthumanism, 2025)
This study explores the motivating factors behind digital activism in Indonesia, focusing on the Save KPK movement as a case study. The movement emerged in response to perceived threats to the independence and effectiveness of the Corruption Eradication Commission (KPK). Using qualitative content analysis of social media campaigns, online petitions, and digital discourse, the study identifies key motivators that drive individuals and communities to engage in digital activism. Findings suggest that motivations are influenced by a combination of moral outrage, political awareness, collective identity, and accessibility of digital platforms. The study also highlights the role of social media in strengthening citizen engagement and mobilizing support across diverse demographics. This research contributes to the understanding of digital political participation in the Global South and underscores the importance of online spaces in contemporary democracy movements.